A delayed diagnosis of X-linked hyper IgM syndrome complicated with toxoplasmic encephalitis in a child: A case report and literature review. Issue 49 (December 2017) - Liu, Xiaoliang; Zhou, Kaiyu; Yu, Dan; Cai, Xiaotang; Hua, Yimin; Zhou, Hui; Wang, Chuan
Abstract: Introduction: The X-linked hyper-immunoglobulin M syndrome (XHIGM) is an uncommon primary combined immunodeficiency disease caused by CD40L gene mutations. A delayed or missed diagnosis of XHIGM is common and concerning, owing to atypical immunoglobulin profile and phenotype of some patients, low recognition, and limited knowledge of clinicians on XHIGM in some underdeveloped areas. Opportunistic infections are a prominent clinical feature of XHIGM. However, toxoplasma encephalitis occurs sporadically and is extremely rare in patients with XHIGM. Diagnostic and therapeutic procedure: A 2 years and 10 months' old male suffered from 3 times of serious infection since 1 year and 4 months of age. Although with history of recurrent respiratory infections, protracted diarrhea, persistent or intermittent neutropenia companioned with oral ulcer, and a typical immunoglobulin profile during his second disease attack, the consideration of XHIGM was still completely ignored because of our low recognition and limited knowledge of this disorder. The diagnosis of XHIGM was ultimately confirmed by detection of elevated serum IgM concentration, decreased serum IgG and IgE concentration, and identification of a mutation c.654C>A (p.C218X) in CD40L gene. Given clinical manifestation of lethargy, uncontrollable somnolence and ataxia, a cat/dog exposure history, positive serum Toxoplasma gondii ( T gondii ) IgM, positive cerebrospinal fluid T gondii PCR results, and typical characteristics of brain magnetic resonance imaging as multiple rings liked nodules lesions in bilateral cerebral hemisphere cortex, bilateral basal ganglia, and dorsal thalamus, the diagnosis of toxoplasmic encephalitis was considered during his third disease attack. Thereafter, oral administration of sulfadiazine and azithromycin, intravenous immunoglobulin, and subcutaneous injection of G-CSF were initiated. Regrettably, the patient abandoned the treatment because of economic factor and died 3 months after discharge. Conclusions: A more thorough clinical history and some features like recurrent respiratory infections, protracted diarrhea, and persistent or intermittent neutropenia companioned with oral ulcer could increase clinical suspicion of XHIGM. Cerebral toxoplasmosis is rare in patients with XHIGM, but still should be considered. The present study firstly reported a delayed diagnosed case of XHIGM with CD40L gene c.654C>A (p.C218X) mutant complicated with toxoplasma encephalitis in Chinese population, which highlighted the importance of CD40-CD40L interaction in cell-mediated immunity against T gondii .